Etika Belajar Dalam Al-Qur’an (Studi Kisah Nabi Musa Belajar Kepada Nabi Khidir Dalam Al-Qur’an) - Heri Khoiruddin (STAI Siliwangi Bandung, 2015)
Qur’an is the main source of ethical teachings, including ethics of student learning to his teacher. Knowing how the ethics of learning in the Qur’an can be traced through various stories. Among stories directly related to the study of ethics is the story of Moses learned to Khidr. Hence, this article is intended to research how the ethics of Moses learned to Khidr. From this research, can be learned what ethics has to be owned and developed by student to his teacher so that the knowledges gained by student become the useful and meaningful sciences for his life.